MRI and Molecular imaging studies of post-prandial gastrointestinal motility and peptide response in health and Crohn’s disease - Khalaf, Asseel (2018)
Introduction: Crohn’s disease (CD) patients suffer postprandial symptoms such as chronic diarrhoea, abdominal pain, bloating, weight loss and nutritional abnormalities. The changes in the regulation of gut hormones and gut dysmotility are believed to play a role but these are rarely studied together in the postprandial state in an unprepared bowel. This project aimed to: (a) develop an MRI methodology to assess fasting and postprandial intestinal motility and gut peptides using a soup test meal intervention in healthy volunteers and (b) to use this methodology to investigate the pathophysiological fasting and postprandial responses in CD.